Assessing the pathogenicity of BRCA1/2 variants of unknown significance: Relevance and challenges for breast cancer precision medicine - De Paolis, Elisa; Paris, Ida; Tilocca, Bruno; Roncada, Paola; Foca, Laura; Tiberi, Giordana; D’Angelo, Tatiana; Pavese, Francesco; Muratore, Margherita; Carbognin, Luisa; Garganese, Giorgia; Masetti, Riccardo; et al. (Frontiers in Oncology, 2023)
Introduction Breast cancer (BC) is the leading cause of cancer-related death in women worldwide. Pathogenic variants in BRCA1 and BRCA2 genes account for approximately 50% of all hereditary BC, with 60-80% of patients characterized by Triple Negative Breast Cancer (TNBC) at an early stage phenotype. The identification of a pathogenic BRCA1/2 variant has important and expanding roles in risk-reducing surgeries, treatment planning, and familial surveillance. Otherwise, finding unclassified Variants of Unknown Significance (VUS) limits the clinical utility of the molecular test, leading to an “imprecise medicine”. Methods We reported the explanatory example of the BRCA1 c.5057A>C, p.(His1686Pro) VUS identified in a patient with TNBC. We integrated data from family history and clinic-pathological evaluations, genetic analyses, and bioinformatics in silico investigations to evaluate the VUS classification. Results Our evaluation posed evidences for the pathogenicity significance of the investigated VUS: 1) association of the BRCA1 variant to cancer-affected members of the family; 2) absence of another high-risk mutation; 3) multiple indirect evidences derived from gene and protein structural analysis. Discussion In line with the ongoing efforts to uncertain variants classification, we speculated about the relevance of an in-depth assessment of pathogenicity of BRCA1/2 VUS for a personalized management of patients with BC. We underlined that the efficient integration of clinical data with the widest number of supporting molecular evidences should be adopted for the proper management of patients, with the final aim of effectively guide the best prognostic and therapeutic paths.